2014
DOI: 10.4103/2230-8210.129110
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin levels in Indian patients with psoriasis and its relation to metabolic syndrome

Abstract: Background:Adiponectin is a cytokine mainly secreted from the adipose tissue, which has insulin-sensitizing effects, antiatherosclerotic actions, and antiinflammatory properties. There are a few studies that have demonstrated that adiponectin is reduced in patients with psoriasis suggesting that this adipocytokine may have a role in the pathogenesis of psoriasis. There have been no studies so far on adiponectin in relation to psoriasis and metabolic syndrome (MetS).Objectives:This study was performed to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recent evidence highlights the important and potentially beneficial role of adiponectin in psoriasis. To begin with, patients with psoriasis have a significantly decreased level of adiponectin compared to healthy controls [ 122 , 123 ]. Secondly, the treatment of psoriasis leads to an elevation of the serum adiponectin level [ 124 ].…”
Section: Adiponectinmentioning
confidence: 99%
“…Recent evidence highlights the important and potentially beneficial role of adiponectin in psoriasis. To begin with, patients with psoriasis have a significantly decreased level of adiponectin compared to healthy controls [ 122 , 123 ]. Secondly, the treatment of psoriasis leads to an elevation of the serum adiponectin level [ 124 ].…”
Section: Adiponectinmentioning
confidence: 99%
“…It can suppress the production of pro-inflammatory cytokines and promote the secretion of anti-inflammatory cytokines ( 14 , 15 ). Studies have shown that adiponectin levels are often decreased in patients with psoriasis ( 16 , 17 ). This reduction in adiponectin level is suggested to contribute to persistent inflammation; however, the mechanisms are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%